Respostas

A melhor resposta!
2014-04-11T15:46:54-03:00
4 x^{2}  - (2k-4)x + 3k - 6 = 0 ⇒ você não colocou o x ao lado do - (2k-4), mas suponho que tenha apenas esquecido...

a)  x_{1} =34. 3^{2} - (2k-4).3 + 3k - 6 = 0

4. 9 - (6k-12) + 3k - 6 = 0

36 - 6k+12 + 3k - 6 = 0

42 - 3k = 0

3k = 42

k=14

b) S= \frac{-[-(2k-4)]}{4} = \frac{(2k-4)}{4} = \frac{k-2}{2} =10k-2=20k=22

c) P= \frac{3k - 6}{4} =83k - 6 =323k =38k= \frac{38}{3}

d) S = 0 S= \frac{-[-(2k-4)]}{4} = \frac{(2k-4)}{4} = \frac{k-2}{2} =0k-2=0k=2

e) P=1P= \frac{3k - 6}{4} =13k - 6 = 43k=10k= \frac{10}{3}
2 5 2